An Analysis of Figurative Language in William Shakespeare’s Selected Poems - Amelia Yuli Astuti; Madhelin Galnesha Junanda (Jurnal Ilmiah Langue and Parole, 2022)
This study analyzes the figure of speech and the meaning contained in the lyrics of selected poetry by William Shakespeare. This research applies semantic theory, especially in figurative language. The theory used in analyzing figurative language is Alvius's theory (2003) the use of meaning in literary works. This study uses a deductive method. The analytical technique used in this study uses analytical techniques. The data collection technique used in this research is the observation technique followed by the note-taking technique. The results showed that the total figurative language used in William Shakespeare's selected poetry was 21 data. Data from figurative language includes 5 metaphorical data, 2 simile data, 2 personification data, 2 hyperbole data, 4 oxymoron data, and 6 polysemy data.